Outcomes of EVAR with the endurant stent-graft system in patients with infrarenal ruptured abdominal aortic aneurysms: Is hostile anatomy a challenging factor?. Issue 11 (November 2015) - Kucukay, Fahrettin; Karan, Adnan; Şimşek, Erdal; Özdemir, Mustafa; Okten, Sarper; Ulus, Ahmet Tulga
Highlights: In this study, primary outcome measures (POM) were procedure-related mortality, 30-day mortality, and survival rate at 1 year in patients with ruptured AAAs and which were treated with Endurant stent-grafts. Secondary outcome measures (SOM) were technical success, open surgical conversion, complications, survival, relationship between size-severity of the rAAA and mortality, procedure time, hospital stay. In patients with rAAAs, the periprocedural EVAR mortality rate was 33%. The overall mortality rate without prehospital phase deaths was 40%. Seventy three percent of the patients with rAAAs had hostile anatomy. This retrospective analysis demonstrated that there were no statistically significant differences between the groups considering POMs and SOMs (except hospital stay). Mean hospital stay was shorter in the normal anatomy group. The presence of a hematoma extending into the pelvis or suprarenal space, or to both sides of the aorta, and free intraperitoneal blood resulted in higher mortality. Fifty four percent of the patients with hostile anatomy survived after the EVAR of rAAAs, without significant major complications. EVAR of rAAAs with hostile anatomy is feasible. Off-label use of Endurant-I endografts could be expanded. Abstract: Purpose: To compare outcomes of endovascular aneurysm repair (EVAR) using the Endurant-I stent-graft system between patients who have ruptured abdominal aortic aneurysms (rAAAs) with normal and hostile anatomy. Materials and methods: Patients with rAAAs who underwent EVAR between January 2008 and March 2014 were included in the study. There were 21 (70%) men and 9 (30%) women with a mean age of 70 years. Multidetector computed tomography (CT) angiography findings of the rAAA were classified according to the "Classification based on CT findings, " and imaging planning was performed according to the Society of Interventional Radiology Guideline. Primary outcome measures (POM) were procedure-related mortality, 30-day mortality, and survival rate at 1 year. Secondary outcome measures (SOM) were technical success, open surgical conversion, complications, survival, relationship between size-severity of the rAAA and mortality, procedure time, hospital stay. Results: The periprocedural-EVAR mortality rate was 33%. The overall mortality rate without prehospital phase deaths was 40.0%. Seventy three percent of the patients with rAAAs had hostile anatomy. There were no statistically significant differences between the groups in POMs and SOMs (except mean hospital stay). Mean hospital stay was shorter in the normal anatomy group. The mortality rate was higher in patients with hematoma in both sides of the aorta and free intraperitoneal hematoma. Conclusion: EVAR of rAAAs with hostile anatomy is feasible and off-label use of Endurant-I endografts could be expanded.